Macrodystrophia Lipomatosa: A Rare Case of Ulnar Nerve Territory Involvement - Ullal, Sonali; Arora, Shivani (Indian Journal of Radiology and Imaging, 2023)
Macrodystrophia lipomatosa (MDL) is a rare congenital, nonhereditary anomaly characterized by overgrowth of all the mesenchymal elements, predominantly the fibroadipose tissue in a sclerotomal distribution commonly involving the median nerve territory in the upper extremity and plantar nerve territory in the lower extremity. It can be either static or progressive, with the former being the more common. MDL is usually present since birth and the affected digit/region increases in length and girth, and growth ceases after puberty. We discuss a rare case of ulnar nerve territory involvement that progressed to grow even after puberty.
Keywords: localized gigantism; macrodystrophia lipomatosa; ulnar territory macrodystrophia lipomatosa